Characterisation and modelling of multipath delay for wireless LAN - Ge, Qi. (2008)
This thesis presents the characterization and modelling of indoor wireless Local Area Network(WLAN) channel at 5GHz and 18GHz band using directive antennas. Wideband propagation measurements, large and small scales, were performed using a vector network analyzer at the foyer of Main Lecture Theatre (MLT), which is similar to an office area.